Verifying goal-oriented specifications used in model-driven development processes. (March 2017) - Giachetti, Giovanni; Marín, Beatriz; López, Lidia; Franch, Xavier; Pastor, Oscar
Abstract: Goal-oriented requirements engineering promotes the use of goals to elicit, elaborate, structure, specify, analyze, negotiate, document, and modify requirements. Thus, goal-oriented specifications are essential for capturing the objectives that the system to be developed should achieve. However, the application of goal-oriented specifications into model-driven development (MDD) processes is still handcrafted, not aligned in the automated flow from models to code. In other words, the experience of analysts and designers is necessary to manually transform the input goal-oriented models into system models for code generation (models compilation). Some authors have proposed guidelines to facilitate and partially automate this translation, but there is a lack of techniques to assess the adequacy of goal-oriented models as starting point of MDD processes. In this paper, we present and evaluate a verification approach that guarantees the automatic, correct, and complete transformation of goal-oriented models into design models used by specific MDD solutions. In particular, this approach has been put into practice by adopting a well-known goal-oriented modeling approach, the i* framework, and an industrial MDD solution called Integranova. Highlights: An approach to verify the completeness of model transformations is defined. The approach is applied to goal-oriented used in MDD processes. The approach provides quantitative information about modeling issues. Counts with a process for the definition of verification and model-fixing artifacts. An experiment is performed to evaluate the verification approach.